Work-Related Musculoskeletal Discomfort and Injury in Microsurgeons - Howarth, Ashley L.; Hallbeck, Susan; Mahabir, Raman C.; Lemaine, Valerie; Evans, Gregory R. D.; Noland, Shelley S. (Journal of Reconstructive Microsurgery, 2019)
Background Long surgical procedures with loupe magnification and microscopes may put microsurgeons at an increased risk of musculoskeletal discomfort. Identifying the prevalence and impact of work-related musculoskeletal discomfort may guide preventive strategies to prolong well-being, job satisfaction, and career duration.Methods An online 29-question survey was designed to evaluate work-related musculoskeletal discomfort. The survey was created and distributed electronically through a private survey research center and was sent to the members of the American Society for Reconstructive Microsurgery.Results There were 117 respondents (16.7% response rate): 80% were men; 69% were aged 31 to 50 years; and 68% were in academic practice. On a scale of 0 to 10 (0, no pain and 10, worst pain), the median for work-related musculoskeletal discomfort for surgery without loupes or microscope was 2; with loupes, 4; and with a microscope, 5. Pain was most common in the neck. Half of the surgeons reported pain within 4 hours of surgery, and 57% feared that pain would influence future surgical performance. Surgeon discomfort affected posture (72%), stamina (36%), sleep (29%), relationships (25%), concentration (22%), and surgical speed (19%). Tremor caused by the discomfort occurred in 8%. Medical treatment for discomfort was sought by 29%. Time off work for treatment occurred for 8%.Conclusion Work-related musculoskeletal discomfort can affect many aspects of a microsurgeon's life and has the potential to limit a surgeon's ability to operate. Therefore, more emphasis is needed in the surgical community on the important issues of occupational health and surgical ergonomics for microsurgeons.
Keywords: microsurgery; occupational pain; injury; surgery; plastic surgery